Financial Management Behavior and Its Impact on Higher Education Performance - Firdausi, Iqbal; Rusqiati, Dini; Hayati, Nurul; Amalia, Henny Septiana (JURNAL AL-TANZIM, 2023)
This study aims to analyze financial management behaviour and its impact on university performance from the perspective of Wealth Management. This study uses a qualitative case study type approach, in which researchers attempt to uncover the meaning behind financial management carried out by universities. Interviews, observations and documentation serve as a medium for collecting research data. Data analysis was carried out through data collection, presentation, and reduction stages and ended with concluding. The study results a show that financial management behaviour at STIE Indonesia Banjarmasin is carried out through financial planning, implementation and evaluation based on the principles of fairness, efficiency, transparency and public accountability. While the impact of financial management behaviour is, first, increasing educational performance; second, increasing research and community service performance and third, increasing public trust in higher education institutions. This research provides implications for the importance of wealth management in the higher education governance system towards superior and competitive tertiary institutions.